The Role of execution teaching competences in the achievement of the session of physical and sports education among the students of the Institute of Sciences and Techniques of Physical and Sports Activities - merniz_amina,; kamel maegag, (sports creativity, 2025)
Title : Role of executiopn teaching competences in the achievement of the session of physical and sports education among the students of the Institute of Sciences and Techniques of Physical and Sports Activities -Study problem: -Do the students of the Institute of Sciences and Techniques of Physical and Sports Activities have competence of evaluation? - Hypotheses: -Students of the Institute of Sciences and Techniques of Physical and Sports Activities have competence of evaluation. Objectives of the study: - To know the importance and the role of practical training in the development of teaching competences among student-trainees. - To know the training needs for the student-trainees by the means of knowing their weak points. - To know if the student-trainees have the competences of evaluation. - Method used: to answer the problem asked in our research, we used the descriptive survey method because it is appropriate to the nature of the subject posed. Indeed, it is the methodology of research the most used in particular in the psychological, educational, social and sports researches. Study population and study sample The research population The population of our research consists of physical and sports education teachers in the secondary schools of the province of M'sila, supervisors in the practical training and students in Master 2 of the Institute of Sciences and Techniques of Physical and Sports Activities, Department of “Education and Motricity”, trainees in these secondary schools